THE ROLE OF NON-VERBAL COMMUNICATION IN LANGUAGE TEACHING - Aliyeva Shahlo Avaz qizi (American Journals Publishing, 2024)
The process of language learning is not only about learning words. In this process, non-verbal communication, i.e. language tools other than words, as well as facial expressions, physical movements and body language play an important role. Nonverbal communication is of particular importance in language learning and can significantly improve students' language comprehension and expression. In this article, we will provide detailed information about the role and importance of non-verbal communication in the language learning process.
Keywords: English language, non-verbal communication, skills, cultural context, culture, facial expressions, physical movements.